EDUKASI PSIKOLOGI PELAYANAN TAMU: MEMBEKALI SISWA MAGANG SMK DI FOUR POINTS BY SHERATON BATAM - Lapotulo, Nensi; Kurnia, Okki; Simatupang, Devid Trinaldo; Saputra, Andre (Batara Wisnu : Indonesian Journal of Community Services, 2025)
This community service activity aims to provide guest service psychology education for vocational high school (SMK) internship students at Four Points by Sheraton Batam. The training is designed with a practical, interactive, and enjoyable approach, covering effective communication, emotional management, empathy, and conflict resolution. Methods employed include interactive workshops, service simulations, and reflective learning sessions. Activity evaluation indicates that the training effectively enhances the skills and confidence of internship students in addressing various guest service challenges, while positively contributing to the hospitality industry in Batam City.